Gambaran Preferensi Media Belajar Mahasiswa Kedokteran Universitas Tarumanagara - Pratama, Alvin Putra; Irawaty, Enny (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2022)
Learning medium are mediums used to convey various learning materials to improve knowledge. One example of a learning medium is books. With the advancement of technology, various books are now available in digital form. The availability of books and learning materials in digital format allows students, especially college students, to use either print format or digital format based on their preferences. This study aim to determine the format preferences of medical students of Tarumanagara University when studying. Descriptive study was conducted on 445 medical students from class of 2018-2020 of Tarumanagara University using the format preference questionnaire that had been modified. Sample were taken using total sampling. The results showed that student’s print format preference during studying were 53,26% while digital format preference were 46,74%. The ease of reading repeatedly with longer duration was the most reason stated by students with print format preferences (43,46%) while the convenience of being able to be read anywhere was the reason stated by students with digital format preference (72,17%). Student’s preference of print and digital format based on language and length of the reading material were questioned as well. The students shows a large preference for print format if the texts are in Bahasa Indonesia (67,42%), while students shows a preference for digital format if the text are presented in foreign language (70,11%). If text’s length are ≥7 page and 7 page, the students prefer to use print format. This study also shows that students have their own techniques/strategies when reading digitally. Underlining/highlighting is the technique mostly used by students (69,66%).From this study, it can be concluded that the majority of Tarumanagara University’s medical students prefers print format rather than digital format for studing purposes, hence Tarumanagara University should provide reading materials in hardcopy to support students academic activites.